UTILIZATION OF FORMOSAT-3/COSMIC GPS RADIO OCCULTATION DATA FOR PRECIPITABLE WATER VAPOR ESTIMATING IN THE ATMOSPHERE - - Noersomadi (Widyariset, 2012)
Utilization of FORMOSAT-3/COSMIC satellite data using GPSRO for atmospheric Precipitable WaterVapor (PWV) estimating has been done. This research analyzed comparison between daily PWV profile from radiosondeand GPSRO observations during 2007. Used radiosonde data were from obervation at Soekarno-HattaAirport, Jakarta. While GPSRO data were determined by finding the nearest occultation locations with radiosondelaunching in the same day. Extrapolation method has been applied for estimating data which were not recordedabove surface. Results showed before and after applying extrapolation method on GPSRO data, the linear correlationbetween PWV derived from both of observations technique are 0.657 and 0.849 respectively. Applicationof PWV from GPSRO was shown in hovmoller diagram during 2 January to 19 May 2011. The estimation duringthat period are between 10 to 55 mm, which described the existence of Madden Julian Oscillation. Hence, theseresults depicted that GPSRO can be utilized for PWV estimation that could be continued to enhance precipitationmodelling.